2005
DOI: 10.1073/pnas.0503399102
|View full text |Cite
|
Sign up to set email alerts
|

Functional similarities between phage λ Orf and Escherichia coli RecFOR in initiation of genetic exchange

Abstract: Genetic recombination in bacteriophage relies on DNA end processing by Exo to expose 3-tailed strands for annealing and exchange by ␤ protein. Phage encodes an additional recombinase, Orf, which participates in the early stages of recombination by supplying a function equivalent to the Escherichia coli RecFOR complex. These host enzymes assist loading of the RecA strand exchange protein onto ssDNA coated with ssDNA-binding protein.In this study, we purified the Orf protein, analyzed its biochemical properties,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
42
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(44 citation statements)
references
References 47 publications
2
42
0
Order By: Relevance
“…An Orfmodified SSB may be a specialized modification that allows RecA to easily displace Beta without interference from SSB. In partial support of this proposal, Maxwell et al (142) found that Orf binds to the E. coli SSB protein.…”
Section: Other λ Functions That Influence the Mechanism Of Red Recombmentioning
confidence: 68%
See 1 more Smart Citation
“…An Orfmodified SSB may be a specialized modification that allows RecA to easily displace Beta without interference from SSB. In partial support of this proposal, Maxwell et al (142) found that Orf binds to the E. coli SSB protein.…”
Section: Other λ Functions That Influence the Mechanism Of Red Recombmentioning
confidence: 68%
“…In addition, the study demonstrated that Orf binds to ssDNA. Using dsDNA substrates containing ssDNA gaps, the authors determined that ssDNA binds to a U-shaped cleft on the surface of the protein rather than going through the central channel (142). They suggested that a fluorescence quench observed when Orf binds ssDNA could indicate a conformational change that allows preferential binding of RecA or Beta.…”
Section: Other λ Functions That Influence the Mechanism Of Red Recombmentioning
confidence: 99%
“…Precisely how these three proteins (wileyonlinelibrary.com) DOI:10.1002/jmr.1079 assemble at dsDNA-ssDNA junctions and promote RecA nucleation is unclear. Some of the in vitro properties of Orf resemble those reported for RecFOR, including binding to DNA and a specific interaction with E. coli SSB, although, Orf does not stimulate annealing of complementary ssDNA molecules (Maxwell et al, 2005). The Orf crystal structure reveals an asymmetric homodimer arranged as a toroid (Maxwell et al, 2005).…”
Section: Introductionmentioning
confidence: 78%
“…Some of the in vitro properties of Orf resemble those reported for RecFOR, including binding to DNA and a specific interaction with E. coli SSB, although, Orf does not stimulate annealing of complementary ssDNA molecules (Maxwell et al, 2005). The Orf crystal structure reveals an asymmetric homodimer arranged as a toroid (Maxwell et al, 2005). Bound ssDNA is predicted to occupy a shallow groove across the protein surface rather than threading through the central channel.…”
Section: Introductionmentioning
confidence: 79%
“…Proteins that facilitate the formation of the filaments of RecA-class recombinases are called recombination mediator proteins (21). Recombination mediator proteins are as ubiquitous as are the recombinases themselves (21,(23)(24)(25)(26)(27)(28). The E. coli RecF, RecO, and RecR proteins are perhaps the prototypical recombination mediator proteins (12, 21, 29 -32), part of a larger network of bacterial proteins that regulate almost every aspect of RecA function (22,30,33).…”
mentioning
confidence: 99%